The underlying contracts of Islamic Banking (IB) products and some related issues in the current practice / Siti Khadijah Ab. Manan and Norlela Kamaluddin. - Ab. Manan, Siti Khadijah; Kamaluddin, Norlela (Universiti Teknologi MARA Cawangan Selangor, 2010)
Ever since the establishment of the first Islamic bank in Malaysia, the progress and development of Islamic banking and finance have been tremendous and commendable. Various Islamic banking products are developed and introduced based on certain Islamic business contracts that comprise uqud al-ishtirak, uqud al muawadat and others. Some products are even developed on hybrid basis while some others are based on controversial or disputable contracts. The tremendous development of the products nevertheless has stirred a string of discussions and arguments as the products are seen as just replication of the conventional products. This paper will therefore attempt to highlight several issues on some of the Islamic banking (IB) products. The underlying contracts and their current applications in Islamic banks are first explained to give preliminary understanding of the issues. It is believed that, by highlighting the issues, some appropriate measures could be explored in future research in order to materialise the true meaning of Islamic banks.